Intimate partner violence, spouse extramarital affairs, and depression among women in rural Uganda - Kaggwa, Mark Mohan; Namatanzi, Brenda; Kule, Moses; Nkola, Rahel; Najjuka, Sarah Maria; Ashaba, Scholastic (Research square, 2021)
Background: Depression is highly prevalent among women compared to men. Women in rural areas are more at risk of depression compared to their peers in urban areas. Some of the factors associated with depression among married women are spouse related factors including extramarital affairs and intimate partner violence (IPV). Objective: To determine the prevalence of depression and factors associated with depression among married women in rural Southwestern Uganda. Methods: This was a cross-sectional study in rural southwestern Uganda among married/cohabiting women aged 18 to 45 years. We used the Patient Health Questionnaire 9 (PHQ-9) to assess for depression, composite abuse scale (Revised) – Short Form (CASR-SF to measure IPV. Logistic regression was used to estimate the associations between depression and several factors including spouse extramarital affair, IPV, and sociodemographic factors. Results: We enrolled 153 women, mean (standard deviation) age of 33.3 (6.7) and the majority were unemployed. The mean number of children between the couple was 4.05 (2.17). More than half (65,4%) had depressive symptoms and 64.1% had experienced intimate spouse violence. The reported spouses’ mean (SD) age was 43.4 (9.5). Almost half (49.65%) were known to be involved in an extramarital affair. There was a statically significant association between depression among women and spouse extramarital affairs (adjusted odds ratio (AOR) 24.93; 95% CI 1.25–498.34]; p-value = 0.04). Conclusion: There was a high prevalence of depression and intimate partner violence among women in rural Uganda. The high prevalence was associated with spouse extramarital affairs. There should be routine screening for depression and intimate partner violence among married women at lower-level health facilities in rural settings especially those whose husbands are involved in extramarital affairs to ensure early diagnosis and access to appropriate mental health care to maintain functionality in society and family level since women are the backbone of their families.
Keywords: Depression; Intimate pattern violence; Married women; Spouse extramarital affairs; Rural Uganda; Women mental health; IPV; Domestic violence; Extramarital relationship